A note on rings with certain variables identities - Hazar Abu-Khuzam (International Journal of Mathematics and Mathematical Sciences)
It is proved that certain rings satisfying generalized-commutator constraints of the form [xm,yn,yn,...,yn]=0 with m and n depending on x and y, must have nil commutator ideal.